Authentic Assessment as a Catalyst for Student Engagement and Contextual Learning: A Qualitative Study of Classroom Practices in Secondary Education - Jelli Anggriana; Maghdahalena Tjalla (Social Sciences and Humanities Reviews, 2026)
Background: Traditional assessment often emphasizes memorization and standardized testing, offering limited insight into students’ ability to apply knowledge in meaningful contexts. Authentic assessment has emerged as an alternative approach that connects evaluation with real-world tasks and more student-centered learning experiences. Aims: This study examined how authentic assessment influences teaching practices, student engagement, and contextual learning in secondary education classrooms. Methods: A qualitative descriptive design was employed. Data were collected through semi-structured interviews and classroom observations involving English teachers from two secondary schools in Indonesia. Participants were selected purposively based on their experience in applying authentic assessment. Data were analyzed through reduction, display, and interpretation to identify recurring themes in classroom practice. Results: The findings show that authentic assessment encouraged more contextual, interactive, and reflective learning. Teachers reported that real-world tasks increased students’ participation in discussion, collaboration, and problem-solving activities. Classroom observations also indicated higher motivation and stronger engagement when students were asked to apply knowledge rather than reproduce information. Conclusion: Authentic assessment functions not only as an evaluation tool but also as a pedagogical driver that supports meaningful learning, critical thinking, and active classroom participation. Its successful implementation, however, depends on teacher readiness, institutional support, and clear assessment criteria. These findings reinforce the relevance of authentic assessment for educational reform and contemporary classroom practice